2020
DOI: 10.1111/1365-2435.13568
|View full text |Cite
|
Sign up to set email alerts
|

Severe coral loss shifts energetic dynamics on a coral reef

Abstract: Declining coral cover and loss of structural complexity are widely reported on today's coral reefs. While coral loss frequently triggers changes in coral reef fish assemblage structure, the ecosystem‐scale consequences of these changes are poorly known. Here we evaluate how four metrics of energy flow and storage that underscore a critical coral reef function, consumer biomass production, respond to severe coral loss on a coral reef in the northern Great Barrier Reef, Australia. We compared fish and benthic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 75 publications
3
56
1
Order By: Relevance
“…However, the lack of difference in benthic community structure observed between regions suggests that benthic structure was at least not a primary driver of the observed patterns. Although the loss of some specialist cryptobenthic species has been reported after substantial live coral cover loss 99,105 , previous studies have not detected substantial short-term changes in either small reef fish richness and abundance or in overarching ecosystem productivity 27,29,31,56,99 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the lack of difference in benthic community structure observed between regions suggests that benthic structure was at least not a primary driver of the observed patterns. Although the loss of some specialist cryptobenthic species has been reported after substantial live coral cover loss 99,105 , previous studies have not detected substantial short-term changes in either small reef fish richness and abundance or in overarching ecosystem productivity 27,29,31,56,99 .…”
Section: Discussionmentioning
confidence: 97%
“…In the wake of losing coral habitat, communities of the most prominent reef consumers, teleost fishes, also decline or shift in composition 24 27 , which directly affects the provision of resources to people dependent on reef fisheries 28 . Although recent evidence suggests that some fish species will be able to cope with (or even benefit from) live coral loss, at least in the short term 28 31 , tropical reef fishes are typically adapted to a relatively narrow suite of environmental conditions. Thus, reef fishes may also be vulnerable to the direct effects of climate change on, for instance, sea surface temperatures 13 , 32 , 33 .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a study in the Seychelles suggested that catch rates of some groupers in Aldabra Atoll declined across a period of climate stress (Pistorius & Taylor, 2009). The biomass and productivity of herbivorous fish has been known to increase with declines in corals, however (McClanahan, Maina, & Pet‐Soede, 2002; Morais et al, 2020). In general, the loss of coral appears to have the largest impact on small‐bodied species that do not greatly influence the metric of fishable biomass (Graham et al, 2008; Graham et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, human impacts override the environmental drivers by influencing reef fish habitat (Williams et al, 2015). For instance, fishing is associated with changes in the benthic cover that could potentially influence both refuge from climate disturbances and fishery production (Robinson et al, 2017; Morais et al, 2020). Thus, there are likely to be various feedback mechanisms between human impacts on habitat and fish populations, making it challenging to understand cause and effect and outcomes on ecosystem functions, such as fishery production (Williams & Graham, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Current models based on ‘fixed’ energy metabolism of individuals imply that survival at higher temperatures requires an increase in energy intake (food) to meet thermally elevated energy demands ( Brown et al, 2004 ; Van der Meer, 2006 ; Sinclair et al, 2016 ; Huey and Kingsolver, 2019 ). Such elevated energy demands occur at the same time that performance becomes suboptimal and food availability is likely limited by reduced production and generally a reduced energy flow through the ecosystem (see Morais et al, 2020 ). However, these energetic constraints can be negated or minimized in animals with flexible or temperature independent metabolic rates that allow the lowering of resting energy demands, as occurs in many gastropods, including T. bacillum .…”
Section: Discussionmentioning
confidence: 99%